Switching characteristics of SRO-MISS devices - Burhanuddin Yeop Majfis,; M. J. Morant, (1991)
The switching characteristics of the Metal-Insulator-Semiconductor-Switch (MISS) device with Silicon-Rich-Oxide (SRO) as the semi-insulating material have been studied at room temperature. The SRO films were deposited by atmospheric pressure chemical vapour deposition (APCvD) at 650°C with SiH4 and N20 reactant gases and N2 carrier. The reactant gas phase ratio, R, varies from 0.09 to 0.25 and the deposition time from 0.6 to 2 minutes